Fast on–off controlling of electrohydrodynamic printing based on AC oscillation induced voltage - Huatan Chen; Junyu Chen; Jiaxin Jiang; Zungui Shao; Guoyi Kang; Xiang Wang; Wenwang Li; Yifang Liu; Gaofeng Zheng (Scientific Reports, 2023)
Abstract Stability control of electrohydrodynamic (EHD) printing technology is urgent needed for efficient fabrication of flexible electronics. In this study, a new fast on–off controlling technology for micro droplets of EHD is proposed by applying an AC induced voltage. The suspending droplet interface is broken through quickly, and the impulse current can be significantly reduced from 527.2 to 50.14 nA, which greatly reduces its negative impact on jet stability. What’s more, time interval of jet generation can be shortened by a factor of three, while not only significantly improving the uniformity of the droplets, but effectively reducing the droplet size from 195 to 104 μm. Moreover, the controllable and mass formation of micro droplets are realized, but also the structure of each droplet is able to be controlled independently, which promoted the development of EHD printing technology in more fields.